PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TRAVEL CV. FLORES SIBOLGA - Rezky Adhinata; Mhd. Shafwan Koto; Sriayu Arita Panggabean (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
This study aims to determine the effect of whether there is an influence of the implementation of Total Quality Management (TQM) and service quality on customer satisfaction at Travel CV. Flores Sibolga. This research was conducted at Travel CV. Flores Sibolga The type of research used in this study is a type of quantitative descriptive research. From the results of the research analysis it can be seen that from the calculation of the research instrument, the results between the X and Y variables are obtained for each item which is declared valid because the total Corrcted item value is greater than the critical r value (0.30). From the calculation of the research data instrument, the results obtained between the variables X and Y are declared reliable because the Cronbach Alpha is above 0.60. From the normality test, all of them show that the distribution of the data does not violate the normality assumption, namely in the form of a bell and the data distribution is close to the diagonal line in the normal curve of the P-P Plot. There is an effect of the implementation of Total Quality Management (TQM) and service quality on customer satisfaction based on the calculation of the coefficient of determination of 68.9%, this means that what occurs in the variation of the dependent variable (service quality) of 68.9% is determined by the independent variable ( Total Quality Management and service quality) and the remaining 31.1% is determined by other variables not discussed in this study, such as variables, infrastructure, price, location and others. From the hypothesis test obtained: Total Quality Management variable has a t statistic value of 6.190 and is greater than t table which is 2.030 (6.190 > 2.030) and Service quality variable has a t statistical value of 6.154 which is greater than t table which is 2.030 (6.154 > 2.030) which means the hypothesis proposed "accepted"